The (re)construction of own identity in nurses' work in Brazil: exploratory study - Ednir Assis Souza; Carmen Fontes de Souza Teixeira; Mariluce Karla Bomfim de Souza; Handerson Silva-Santos; Tatiane Araújo-; José Lúcio Costa Ramos
ABSTRACT Objective: To analyse a professional trajectory and how identity conformations of a group of nurses in professional practice in Brazil. Methods: Qualitative study that used the in-depth interviews with nurses in professional practice from 1998 to 2014. Seven nurses working in the various organizational areas of the health systems participated and 3 nurses working in educational and research institutions. The narratives were analyzed in the light of Claude's Dubar theoretical framework and the content analysis technique. Results: The findings demonstrate that career choice is associated with employability, giving little identity. The findings demonstrate that career choice is associated with employability, giving little identity. The formative processes contribute to the (re) construction of identity, as they have produced an anticipation of the future trajectory, identification of job opportunities, recognition, prestige and self-esteem. The care dimension gives greater identity to the workers. Conclusion: The study brings important elements for reflection on the determinants that affect the continuous reconstruction of professional identity, in view of the changes that have been operating in the labor market, in vocational training and in the work of nurses.